2021
DOI: 10.1101/2021.02.21.21252160
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Endothelium-protective, histone-neutralizing properties of the polyanionic agent defibrotide

Abstract: Neutrophil-mediated activation and injury of the endothelium play a role in the pathogenesis of diverse disease states ranging from autoimmunity to cancer to COVID-19. Neutralization of cationic proteins (such as neutrophil extracellular trap/NET-derived histones) with polyanionic compounds has been suggested as a potential strategy for protecting the endothelium from such insults. Here, we report that the FDA-approved polyanionic agent defibrotide (a pleotropic mixture of oligonucleotides) directly engages hi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…Pertinent to our studies, DF has been shown to dampen inflammatory activity of monocytes and neutrophils both known contributors to IPS and ARDS. Specifically, Shi and colleagues recently established that DF mitigates pyroptosis-mediated cell death by binding neutrophil extracellular trap (NET)-derived histones in an in vitro model of neutrophil-mediated activation and injury of the endothelium (26). In addition, in vitro models demonstrate that DF can reduce adhesion molecule expression on ECs or leukocyte adhesion in the context of inflammation engendered by sera from patients with acute GVHD or TNFa respectively (29, 61).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pertinent to our studies, DF has been shown to dampen inflammatory activity of monocytes and neutrophils both known contributors to IPS and ARDS. Specifically, Shi and colleagues recently established that DF mitigates pyroptosis-mediated cell death by binding neutrophil extracellular trap (NET)-derived histones in an in vitro model of neutrophil-mediated activation and injury of the endothelium (26). In addition, in vitro models demonstrate that DF can reduce adhesion molecule expression on ECs or leukocyte adhesion in the context of inflammation engendered by sera from patients with acute GVHD or TNFa respectively (29, 61).…”
Section: Discussionmentioning
confidence: 99%
“…Defibrotide (DF) is an agent FDA approved for the treatment of patients who develop VOD/SOS after BMT that is associated with either renal or pulmonary dysfunction. Importantly, DF has been shown to have properties that stabilize and protect ECs from injury and activation (26)(27)(28)(29). We therefore explored the effects of DF administration in established models of BMT and non-BMT acute lung injury to determine whether DF can modulate markers of lung inflammation and EC activation (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…One of the major components of NETs are histones, and they are known to promote endothelial cell activation (222). It has recently been shown that endothelial cell activation induced by histones can be inhibited by defibrotide, a mixture of oligonucleotides currently used in the treatment of hepatic veno-occlusive disease (223,224). Interestingly, a recent study showed that endothelial cell activation induced by COVID-19 patients' serum could be partially inhibited by defibrotide in vitro (224).…”
Section: Therapeutic Perspectivesmentioning
confidence: 99%
“…It has recently been shown that endothelial cell activation induced by histones can be inhibited by defibrotide, a mixture of oligonucleotides currently used in the treatment of hepatic veno-occlusive disease (223,224). Interestingly, a recent study showed that endothelial cell activation induced by COVID-19 patients' serum could be partially inhibited by defibrotide in vitro (224). NETs, which play an important role in thrombus propagation and stabilization, can be degraded by nucleases, such as DNase 1 (225).…”
Section: Therapeutic Perspectivesmentioning
confidence: 99%